Oral Tranexamic Acid for the Treatment of Melasma - Karn, D; KC, S; Amatya, A; Razouria, EA; Timalsina, M (Kathmandu University Medical Journal, 2014)
Background Melasma poses a great challenge as its treatment is unsatisfactory and recurrence is high. Treatment of melasma using tranexamic acid (oral, topical or intralesional) is a novel concept. Objective To compare the efficacy of oral tranexamic acid with routine topical therapies for the treatment of melasma. Methods It is a prospective, interventional, randomized controlled trial conducted among 260 melasma patients. Patients were divided into two groups consisting of 130 patients each. First group (Group A) was given routine treatment measures and oral Tranexamic Acid while second group (Group B) was treated only with routine topical measures. Capsule Tranexamic Acid was prescribed at a dose of 250 mg twice a day for three months and cases were followed for three months. Response was evaluated on the basis of Melasma Assessment Severity Index (MASI). Mean scores between the two groups were then compared. Results Statistically significant decrease in the mean Melasma Assessment Severity Index from baseline to 8 and 12 weeks was observed among group A patients (11.08±2.91 vs 8.95±2.08 at week 8 and vs. 7.84±2.44 at week 12; p